Clinical evaluation of a gingiva-coloured material, Comp Natur: a 3-year longitudinal study - (:unkn) unknown (My University, 2011)
OBJECTIVE: To report on a three-year clinical evaluation of the gingiva-coloured compomer (Comp Natur, Voco, Germany). METHODS: Twelve patients with cervical lesions as a result of either gingival recession or worn root dentine were included in this study. In total, 106 restorations were evaluated by two examiners at baseline, 6-month and 3-year recalls. RESULTS: Ninety-nine restorations (99/106, 93.4%) were reported with having a good retention in the oral cavity at the 3-year recall. Ninety-two of the 99 restorations were evaluated as excellent for colour match. Marginal discoloration was slightly higher at the 3-year recall, while surface texture and anatomic form were significant. Marginal adaptation was not statistically important at the 3-year recall. There was no problem related to caries and postoperative sensitivity. CONCLUSION: Comp Natur is an acceptable treatment choice for cervical defects with recessed gingiva.
Keywords: Adult; Female; Humans; Middle Aged; Patient Satisfaction; Statistics, Nonparametric; Dentin-Bonding Agents; Dental Restoration, Permanent; Methacrylates; Gingival Recession; Tooth Cervix; Color; Compomers; Dentin Sensitivity